A Thermostabilized, One-Step PCR Assay for Simultaneous Detection of Klebsiella pneumoniae and Haemophilus influenzae - Khazani, Nur Amalina; Nik Mohd Noor, Nik Zuraina; Chan, Yean Yean; Hasan, Habsah; Md Noor, Siti Suraiya; Mohamad, Suharni (Hindawi Publishing Corporation, 2017)
Klebsiella pneumoniae and Haemophilus influenzae are two common pathogens associated with respiratory tract infections. The identification of these pathogens using conventional molecular diagnostic tests requires trained personnel, cold-chain transportation, and storage-dependance, which does not render them user-friendly. The aim of this study was to develop a thermostabilized, cold-chain-free, one-step multiplex PCR for simultaneous detection of K. pneumoniae and H. influenzae. The multiplex PCR assay was designed to amplify the php gene of K. pneumoniae (202 bp) and p6 gene of H. influenzae (582 bp). In addition, the specific primer to amplify glm gene of Helicobacter pylori (105 bp) was included as an internal amplification control. Subsequently, the designed primers and all PCR reagents were thermostabilized by lyophilization. The stability of the thermostabilized PCR was evaluated using the Q10 method. The sensitivity and specificity of performances for thermostabilized PCR were evaluated using 127 clinical isolates and were found to be 100% sensitive and specific.The thermostabilized PCR mix was found to be stable for 30 days and the Q10 accelerated stability was found to be 3.02 months. A cold-chain-free, PCR assay for easy, rapid, and simultaneous detection of K. pneumoniae and H. influenzae was successfully developed in this study.